Strengthening the occupational and social participation of multiple sclerosis patients - design of a multicenter, parallel-group randomized controlled trial (MSnetWork-study) - Meyer-Moock, Sandra; Raths, Susan; Strunk, Katharina; Siebert, Bernward; Hinkfoth, Katrin; Weih, Markus; Fleßa, Steffen; Kohlmann, Thomas (BMC neurology, 2022)
Background Multiple Sclerosis is an autoimmune inflammatory disease of the central nervous system that often leads to premature incapacity for work. Therefore, the MSnetWork project implements a new form of care and pursues the goal of maintaining or even improving the state of health of MS patients and having a positive influence on their ability to work as well as their participation in social life. A network of neurologists, occupational health and rehabilitation physicians, psychologists, and social insurance suppliers provide patients with targeted services that have not previously been part of standard care. According to the patient’s needs treatment options will be identified and initiated. Methods The MSnetWork study is designed as a multicenter randomized controlled trial, with two parallel groups (randomization at the patient level with 1:1 allocation ratio, planned N = 950, duration of study participation 24 months). After 12 months, the patients in the control group will also receive the interventions. The primary outcome is the number of sick leave days. Secondary outcomes are health-related quality of life, physical, affective and cognitive status, fatigue, costs of incapacity to work, treatment costs, out-of-pocket costs, self-efficacy, and patient satisfaction with therapy. Intervention effects are analyzed by a parallel-group comparison between the intervention and the control group. Furthermore, the long-term effects within the intervention group will be observed and a pre-post comparison of the control group, before and after receiving the intervention in MSnetWork, will be performed. Discussion Due to the multiple approaches to patient-centered, multidisciplinary MS care, MSnetWork can be considered a complex intervention. The study design and linkage of comprehensive, patient-specific primary and secondary data in an outpatient setting enable the evaluation of this complex intervention, both on a qualitative and quantitative level. The basic assumption is a positive effect on the prevention or reduction of incapacity for work as well as on the patients’ quality of life. If the project proves to be a success, MSnetWork could be adapted for the treatment of other chronic diseases with an impact on the ability to work and quality of life. Trial registration The trial MSnetWork has been retrospectively registered in the German Clinical Trials Register (DRKS) since 08.07.2022 with the ID DRKS00025451 .